PERBEDAAN EFEKTIVITAS METODE CERAMAH DENGAN METODE PEER EDUCATION TERHADAP PENGETAHUAN REMAJA TENTANG HIV/AIDS TAHUN 2013 - Suryaningsih, Komang (Coping: Community of Publishing in Nursing; Vol 2 No 1 (2014): JURNAL EDISI JANUARI-APRIL 2014, 2014)
Number of people infected with HIV/AIDS in Bali continues to increase. In August 2012 since 1987, cases of HIV/AIDS were recorded in Bali reached 6,504 cases, Denpasar city was ranked first by the number of cases in 2611. In Bali, about 130 adolescent aged 15-19 tested positive for HIV/AIDS until August 2012. Health education will be very useful to improve the knowledge of adolescents about HIV/AIDS when applied through appropriate methods. This study aimed to determine differences in effectiveness of the lecture methods with peer education methods on adolescent knowledge about HIV/AIDS at SMKN 3 and SMKN 4 Denpasar. This study is a quasi experimental study (nonequivalent control group design). The sample consisted of 40 adolescents were selected by quota sampling, divided into two groups: control and experimental groups. The control group is lecture methods and the experimental group is peer education methods. The data was collected using a questionnaire with multiple choice type questions. The results are mean-average knowledge after treatment in lectures group is 74.30 and 79.50 in peer education group. Based on t test this difference was statistically significant with a significance level of p=0.003 (p <0.05) that means there are differences in the effectiveness of the lecture methods with peer education methods on adolescent knowledge about HIV/AIDS in 2013 at SMKN 3 and SMKN 4 Denpasar. Based on the results of this study are expected that peer education methods can be a new methods in health education that effective to increase adolescent knowledge about HIV/AIDS either by health workers, teachers and KPA. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Knowledge, HIV/AIDS; Lecture Methods; Peer Education Methods